1962
DOI: 10.1172/jci104586
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Side-to-Side Portacaval Shunt on Hepatic Hemodynamics in Cirrhosis*

Abstract: Since various types of surgical portal-systemic venous anastomoses are employed in the treatment of portal hypertension, it is of interest to know the effect of these operations on hepatic hemodynamics.There is general agreement that the major hepatic hemodynamic disturbance in cirrhosis is an increase in vascular resistance in the liver, together with an increase in portal venous pressure, and a variable, moderate reduction in hepatic venous blood flow. The fact that wedged hepatic vein pressure is increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
3

Year Published

1964
1964
1988
1988

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 8 publications
1
8
0
3
Order By: Relevance
“…Studies at the time of portacaval shunt by our surgical colleagues, Mikkelsen, Turrill, and Pattison, also indicated less extraction of oxygen and BSP from backflowing portal blood than from hepatic venous blood (10). Our catheterization data suggest a greater decrease in hepatic oxygen uptake after SS shunt than after ES shunt (8). After the oxygen and BSP samples had been obtained, the catheter was again passed into the wedged portal position to repeat the measurement of wedged portal pressure and to confirm the wedged position by the injection through the catheter of 3 to 4 ml of 50%o Hy It fell in all instances after opening the shunt, averaging then 22 cm saline.…”
supporting
confidence: 60%
See 4 more Smart Citations
“…Studies at the time of portacaval shunt by our surgical colleagues, Mikkelsen, Turrill, and Pattison, also indicated less extraction of oxygen and BSP from backflowing portal blood than from hepatic venous blood (10). Our catheterization data suggest a greater decrease in hepatic oxygen uptake after SS shunt than after ES shunt (8). After the oxygen and BSP samples had been obtained, the catheter was again passed into the wedged portal position to repeat the measurement of wedged portal pressure and to confirm the wedged position by the injection through the catheter of 3 to 4 ml of 50%o Hy It fell in all instances after opening the shunt, averaging then 22 cm saline.…”
supporting
confidence: 60%
“…In hepatic venous catheterization studies before and after SS shunt, we found a fall in splanchnic oxygen consumption from a mean of 52 ml per minute to a mean of 32 ml per minute (8). Al If our interpretation of our observations is correct, there should be little difference between the hemodynamic effects of SS and ES shunt in most patients.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations